2020
DOI: 10.1049/iet-epa.2019.0963
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional finite‐element analysis multiphysics modelling of electromagnetic Joule heating in carbon fibre composites

Abstract: This study investigates the possibility of electromagnetic heating of carbon fibre composites (CFCs) to the resin curing temperature, utilising Joule heating, with the main potential application being the on‐site and in‐situ repair of damaged CFCs. The study describes the energy conversion from the supplied AC electrical current to the power generated and hence, heat produced in a CFC. This is investigated through the development of three‐dimensional (3D) finite‐element multiphysics models using a homogenous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…UD material can be heated using magnetic induction when used in a quasi-isotropic layup sequence, so there are conductive pathways between fibres at each layer through thickness. A study by Khan et.al [129] showed that the heating response of a quasi-isotropic layup subjected to magnetic induction is more isotropic than if the plies were stacked in purely UD configuration which showed an anisotropic heating response. In both cases, it was shown that the fibres could be heated to 177 • C which would allow the curing of most aerospace epoxies.…”
Section: Magnetic Induction 241 Background To Magnetic Induction Heatingmentioning
confidence: 99%
“…UD material can be heated using magnetic induction when used in a quasi-isotropic layup sequence, so there are conductive pathways between fibres at each layer through thickness. A study by Khan et.al [129] showed that the heating response of a quasi-isotropic layup subjected to magnetic induction is more isotropic than if the plies were stacked in purely UD configuration which showed an anisotropic heating response. In both cases, it was shown that the fibres could be heated to 177 • C which would allow the curing of most aerospace epoxies.…”
Section: Magnetic Induction 241 Background To Magnetic Induction Heatingmentioning
confidence: 99%
“…Examples of localized heating in the literature include applications to curing processes, 8,9 composite repair, 10 laminate consolidation, 11 and post-consolidation thermoforming of composite parts. 12,13 Localized heating modes used were inductive, 9 microwave irradiation, 7 infrared, 11,14 surface contact, 15 and resistive. 8,10,12…”
Section: Introductionmentioning
confidence: 99%
“…Examples of localized heating in the literature include applications to curing processes, 8,9 composite repair, 10 laminate consolidation, 11 and post-consolidation thermoforming of composite parts. 12,13 Localized heating modes used were inductive, 9 microwave irradiation, 7 infrared, 11,14 surface contact, 15 and resistive. 8,10,12 Examples of applications of local heating to C-FRTS composite parts found in the literature focused on developing methods to reach curing temperatures.…”
Section: Introductionmentioning
confidence: 99%